Price-management of traffic congestion: Hong Kong's Lion Rock Tunnel. Issue 4 (December 2017) - Cao, K.H.; Cheng, Y.S.; Woo, C.K.
Highlights: We develop a Generalized Leontief demand system to estimate various types of vehicles tunnel usage patterns in Hong Kong. Our study documents that the toll-sensitivity of tunnel usage is direction-dependent. We study the potential impacts of two revenue-neutral toll proposals. Abstract: Hong Kong drivers face rush-hour traffic congestion at the Lion Rock Tunnel (LRT) which interconnects the Northeast New Territories and the Kowloon Peninsula. The LRT's flat toll is HK8 (≈US1.03), much lower than the Tate's Cairn Tunnel's (TCT's) vehicle-differentiated tolls of HK13 to HK34 per vehicular trip. We develop two proposals to raise the LRT's toll and reduce the TCT's tolls. Using the monthly data available from the Hong Kong Transport Department for the 15-year period of 2000–2014, we estimate a Generalized Leontief demand system to document statistically significant ( p -value < 0.05) tunnel usage responses to these toll proposals. As the two tunnels' elasticity estimates vary by traffic direction, a directional toll proposal may further ease the LRT's rush-hour congestion. Hence, Hong Kong can price-manage the LRT's congestion because a decrease in the LRT's total usage likely reduces the LRT's peak usage that occurs during the rush hours.